Study of the Correlation between Qur’an and Hadith Learning Outcomes with the Attitude of Religious Moderation in Islamic Senior High School - Tyas Ayu Setiawati; Efi Tri Astuti (JIE (Journal of Islamic Education), 2025)
The purpose of this research is to determine the implementation of religious moderation material in Quran Hadith learning and to understand the relationship between Qur’an Hadith learning outcomes and students' attitudes towards religious moderation. This research using a descriptive quantitative approach. Data collection techniques using questionnaires, observations, and documentation. Instrument testing with validity and reliability tests. Data analysis with prerequisite tests (normality, linearity, and homogeneity tests) followed by the pearson correlation test. This test was chosen to examine the hypothesis of whether there is a relationship between Qur’an Hadith learning outcomes and students' attitudes towards religious moderation. The findings indicate that although there is an implementation of religious moderation material in the learning process, no significant relationship was found between the learning outcomes of the Qur’an and Hadith and the religious moderation attitudes of MA Muhammadiyah 3 Ketro students. Significance value: 0.682>0.05 and correlation coefficient: 0.084 indicate no significant relationship and a very weak correlation. It is concluded that the Ho is accepted, meaning there is no significant correlation between Qur’anic hadith learning outcomes and students' attitudes towards religious moderation. The limitation of this study is that it only uses a sample from one institution, so the results cannot be generalized. The implications of this research indicate the need for the development of a more comprehensive curriculum to enhance religious moderation attitudes. The originality of this research lies in its focus on linking the study of the Qur’an and Hadith with the attitude of religious moderation in Muhammadiyah institutions.